2017
DOI: 10.1186/s12889-017-4951-y
|View full text |Cite
|
Sign up to set email alerts
|

Healthy apple program to support child care centers to alter nutrition and physical activity practices and improve child weight: a cluster randomized trial

Abstract: Background: North Carolina Nutrition and Physical Activity Self-Assessment for Child Care (NAP SACC) resources improve child body mass index (BMI) when the resources are introduced by nurses to child care providers, and offered with workshops and incentives. In San Francisco, public health and child care agencies partnered to adapt NAP SACC resources into an annual "Healthy Apple" quality improvement program (HAP). Methods: This cluster randomized controlled trial pilot-tested integration of the HAP with bi-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(50 citation statements)
references
References 22 publications
1
49
0
Order By: Relevance
“…These reviews highlight that the most effective intervention strategies incorporate both family and the school/childcare environment. Our findings concur with this; we have also found that interventions including a policy-based change to improve the food environment are effective at improving outcomes (Hodgkinson et al, 2019;Natale et al, 2017;Stookey et al, 2017).…”
Section: Quality Of Included Studiessupporting
confidence: 91%
See 3 more Smart Citations
“…These reviews highlight that the most effective intervention strategies incorporate both family and the school/childcare environment. Our findings concur with this; we have also found that interventions including a policy-based change to improve the food environment are effective at improving outcomes (Hodgkinson et al, 2019;Natale et al, 2017;Stookey et al, 2017).…”
Section: Quality Of Included Studiessupporting
confidence: 91%
“…The studies were assessed using the T A B L E 4 (Continued) Daniels et al, 2013;Fisher et al, 2019;Fitzgibbon et al, 2011;Helle et al, 2019;Kim et al, 2019;Natale et al, 2014Natale et al, , 2017Nyström et al, 2017;Quattrin et al, 2014;Skouteris et al, 2016;Tomayko et al, 2016;Wall et al, 2019). | 23 of 31 et al, 2021;Bocca et al, 2012;Campbell et al, 2013;de la Haye et al, 2019;Fitzgibbon et al, 2011;Haines et al, 2018;Hodgkinson et al, 2019;Lumeng et al, 2017;Martínez-Andrade et al, 2014;Natale et al, 2014Natale et al, , 2017Nyström et al, 2017;Quattrin et al, 2014;Salazar et al, 2014;Sherwood et al, 2015;Skouteris et al, 2016;Stark et al, 2011;Stookey et al, 2017;Tomayko et al, 2016;Verbestel et al, 2014;Walton et al, 2015), four of which included policies to promote changes to the early years/childcare setting (Hodgkinson et al, 2019;Natale et al, 2014Natale et al, , 2017Stookey et al, 2017). Five studies focused on modifying diet only (Daniels et al, 2013;Fisher et al, 2019;…”
Section: Study Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…While this cost may be insurmountable for small programs, it can be more feasible as part of state level budgets or as part of large public health initiatives. One such example is the San Francisco Department of Public Health, which uses the Veggie Meter ® to assess the Healthy Apple Program [54,55]. In the specific case of this group, the cost of the device was split across departmental funding and state funding through CFHL, UC.…”
Section: Discussionmentioning
confidence: 99%